Apoptose na eliminação pulpar durante a reabsorção radicular fisiológica de dentes decíduos humanos - Luciana Villela Rodrigues (2008)
Fifty healthy human teeth pulp samples were studied to evaluate the role of apoptosis in pulp elimination during physiological root resorption. The samples were splitted in two groups: a group of deciduous teeth (n=30), with physiological root resorption, and a control group (n=20), with pulps of permanent superior third molar teeth, which do not undergo physiological root resorption. All the teeth already had extraction indicated by other reasons. The pulp samples were processed for routine histological examination and were submitted to morphometrical analysis. Also DNA was extracted and an agarose gel electrophoresis of the genomic DNA was performed. Apoptotic cells were quantified by morphology and confirmed by in situ detection of the genomicfragmentation (TUNEL) and by the ladder pattern at the DNA electrophoresis. The apoptotic index of the group of deciduous teeth (51,01±0,52) was significantly higher than in the control group (25.32± 0,68) (P<0.001). TUNEL Reaction showed intense and diffuse labeling in samples of deciduous teeth, which were not present in controls. The ladder pattern at the DNA electrophoresis was evident in samples of deciduous teeth, and not present in controls. These results seem to indicate a role of apoptosis in pulp elimination during the physiological radicular resorption of human deciduous teeth.